The Covid-19, Policy, and Islamic Capital Market in Indonesia - Retnoningsih, Sri; Naufa, Ahmad Maulin; Astuti, Wulan Budi (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2022)
This paper examines the impact of Covid-19 (death and positive cases) on Indonesia's Islamic capital market, proxied by the Jakarta Islamic Index. Covid-19 data in Indonesia, which is proxied by four measures such as the number of new cases (NC), cumulative cases (CC), new deaths (ND), and cumulative deaths (CD). Further, whether any policy from regulators could mitigate its impact, we utilize daily time-series data from January to July and propose the multiple regression model to test its effect with some robustness checks. Our results indicate that Covid-19 leads to a lower price of the Islamic index, and the regulations from the government could reduce its negative impact. The negative impact of Covid-19 could be reduced by policies from the Indonesian government and other authorities like OJK, IDX, and BI. The policy from those regulators is grouped by policy backgrounds such as lockdowns and restrictions, reopening economy like new normal, fiscal, monetary, and macroeconomic, exchange rate, and balance of payments. Therefore, it is pivotal to alleviate Covid-19’s drawbacks on the Islamic capital market by providing relevant policies in Indonesia.